2013
DOI: 10.3390/ma6125763
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Nanomaterials-Based Fluorescence Spectroscopic and Matrix-Assisted Laser Desorption/Ionization (MALDI) Mass Spectrometric Approaches to Proteome Analysis

Abstract: Semiconductor quantum dots (QDs) or nanoparticles (NPs) exhibit very unusual physico-chemcial and optical properties. This review article introduces the applications of semiconductor nanomaterials (NMs) in fluorescence spectroscopy and matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) for biomolecule analysis. Due to their unique physico-chemical and optical properties, semiconductors NMs have created many new platforms for investigating biomolecular structures and information in modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…[1][2][3] Compared with organic dyes, the QDs seemed more promising in biological analysis because of their broad, tunable, stronger and narrower symmetrical emission spectrum and relatively stable photochemical properties. However, the traditional QDs with excellent optical properties are harmful to the biological species because the inevitable leakage of heavy metals severely affects the human health.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Compared with organic dyes, the QDs seemed more promising in biological analysis because of their broad, tunable, stronger and narrower symmetrical emission spectrum and relatively stable photochemical properties. However, the traditional QDs with excellent optical properties are harmful to the biological species because the inevitable leakage of heavy metals severely affects the human health.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the signal intensities of target analytes were greatly increased because of strong interactions (electrostatic, covalent and hydrophobic) between biomolecules and NPs, which facilitates to absorb greater number of target analytes onto the surfaces of NPs. These approaches provided straightforward miniaturized sample preparation tools for the analysis of peptides, proteins and digested proteins with reduced sample volumes [7,20]. As a result, the detection limits as low as nM-pM were achieved.…”
Section: Maldi-msmentioning
confidence: 99%
“…Recent years, the extraordinary properties of nanomaterials have sparked tremendous interest to use them as probes (sample preparation, separation, imaging and sensing) in analytical techniques for the analysis of a wide range of target analytes (biomolecules, inorganic, organic and drugs) by using various analytical techniques such as UV-visible spectroscopy, fluorescence spectrometry and chromatographic techniques [2][3][4]. Consequently, nanoparticles (NPs) integrated with MALDI-MS technique have been raised as an exciting technique which can be applied in multidisciplinary research fields including biology, clinical, polymers and environmental sciences [5][6][7]. The analytical potential of NPs as biomolecule probes in MALDI-MS was first discovered by Tanaka's group in 1988 [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles provided background‐free or low‐interference spectra, offered high sensitivity, required tiny amounts of material, provided soft ionization compared to conventional matrices such as organic acids or bases, showed multifunctionality such as biochip for separation, could be used for quantification and as a probe for preconcentration and were suitable for post‐synthetic modification for selective investigation . Quantum dots (QDs) have been applied for SALDI‐MS for detection of metallodrugs, protein and peptide analysis, blood fingermarks, and protein quantification (molecular weight (MW) <20 kDa) . However, few studies have paid attention to the effect of surface modification .…”
mentioning
confidence: 99%